Shuttle views the Earth : clouds from space - Jones, Pat, 1948 October 19- (Lunar and Planetary Institute, 1986)
LPI slide set converted to a PowerPoint set by the staff of the Spacecraft Planetary Imaging Facility, Cornell University Informative and visually impressive cloud photographs taken from the shuttle. compiled by Pat Jones Meteosat View of Red Sea Region--Jet Stream Cirrus--GOES View of Eastern United States--Florida Squall Line--Brazil, Thunderstorms--Cumulus Cloud Tops--Field of Cumulonimbus--Cloud Margin, Bering Sea--Overlying Weather Systems--Coastal Current, Namibia--Unique Cloud Lanes, Oman--Jet Stream Cirrus, Saudi Arabia--Sharp-Edged Cirrus, Namibia--Jet Stream Convergence--Cloud Streets, Tiladumati Atoll, Maldive Islands--Cuba, Land-Sea Breeze--Hawaii, Island Wake--Hawaii Cloud Arc--Cloud-Shrouded Volcanos, Galapagos Islands--Von Karman Vortices, Baja California--Cloud Tail, Lake Tana--Lake-Driven Snow--Open Cells Over Ocean--Donut Cloud--Cold Core Eddies--Decaying Tropical Storm--Anticyclonic Clouds--Typhoon Odessa--Eye of Hurricane Kamysi--Typhoon Odessa--Two Fujiwara Typhoons--Golden Sunrise--Agricultural Burning, Madagascar--Agricultural Burning, Malawi--Sunrise--Point Source Dust Storm--Hawaiian Volcanic Eruption Plume--Kelvin Wakes--Weather System Margin--Query Cloud.